Stillbirths: rates, risk factors, and acceleration towards 2030. Issue 10018 (6th February 2016) - Lawn, Joy E; Blencowe, Hannah; Waiswa, Peter; Amouzou, Agbessi; Mathers, Colin; Hogan, Dan; Flenady, Vicki; Frøen, J Frederik; Qureshi, Zeshan U; Calderwood, Claire; Shiekh, Suhail; Jassir, Fiorella Bianchi; et al.
Summary: An estimated 2·6 million third trimester stillbirths occurred in 2015 (uncertainty range 2·4–3·0 million). The number of stillbirths has reduced more slowly than has maternal mortality or mortality in children younger than 5 years, which were explicitly targeted in the Millennium Development Goals. The Every Newborn Action Plan has the target of 12 or fewer stillbirths per 1000 births in every country by 2030. 94 mainly high-income countries and upper middle-income countries have already met this target, although with noticeable disparities. At least 56 countries, particularly in Africa and in areas affected by conflict, will have to more than double present progress to reach this target. Most (98%) stillbirths are in low-income and middle-income countries. Improved care at birth is essential to prevent 1·3 million (uncertainty range 1·2–1·6 million) intrapartum stillbirths, end preventable maternal and neonatal deaths, and improve child development. Estimates for stillbirth causation are impeded by various classification systems, but for 18 countries with reliable data, congenital abnormalities account for a median of only 7·4% of stillbirths. Many disorders associated with stillbirths are potentially modifiable and often coexist, such as maternal infections (population attributable fraction: malaria 8·0% and syphilis 7·7%), non-communicable diseases, nutrition and lifestyle factors (each about 10%), and maternal age older than 35 years (6·7%). Prolonged pregnancies contribute to 14·0% of stillbirths. Causal pathways for stillbirth frequently involve impaired placental function, either with fetal growth restriction or preterm labour, or both. Two-thirds of newborns have their births registered. However, less than 5% of neonatal deaths and even fewer stillbirths have death registration. Records and registrations of all births, stillbirths, neonatal, and maternal deaths in a health facility would substantially increase data availability. Improved data alone will not save lives but provide a way to target interventions to reach more than 7000 women every day worldwide who experience the reality of stillbirth.